PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VII SMP NEGERI 11 MAKASSAR - Rosdiana (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: The Effect of Discovery Learning Model on the Ability to Write Explanatory Texts for Class VII Students of SMP Negeri 11 Makassar. This study aimed to determine the effect of discovery learning model on the ability to write explanatory text students in class VII. This research was conducted at SMP Negeri 11 Makassar. Researcher used the Pre-Experimental research method with the One-Group Pretest-Posttest Design. The population of this research was all grade VII students of SMP Negeri 11 Makassar. This research was conducted in two stages of assessment, namely the initial test or before treatment and the final test or after treatment. Researcher conducted data collection using test and observation methods. The results showed that the ability to write explanatory texts before being given a treat obtained an average value of 69.5 or an incomplete percentage of 59%. After being given treatment by using the discovery learning model learning get an average value of 80.27 with a percentage of 78% that was complete. Improvement of students' writing skills after being given treatment by 78% which was previously 59%. In other words, there was the effect of discovery learning learning model on the ability to write explanatory text for grade VII students of SMP Negeri 11 Makassar.